2016
DOI: 10.1248/bpb.b15-00734
|View full text |Cite
|
Sign up to set email alerts
|

Detecting mRNA Predictors of Acetaminophen-Induced Hepatotoxicity in Mouse Blood Using Quantitative Real-Time PCR

Abstract: Acetaminophen (APAP) is a widely used analgesic and antipyretic drug. Drug-induced liver injury from agents such as APAP is known to vary between individuals within a species. To avoid liver injury and ensure the proper use of pharmaceutical products, it is important to be able to predict such risks using genetic information. This study evaluated the use of quantitative real-time polymerase chain reaction (RT-qPCR) to identify mRNAs (carried in the blood of male ddY mice) capable of predicting susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…On the other hand, when inflammation was caused by hepatic damage, anti-inflammatory cytokines as well as pro-inflammatory cytokines were induced 37 , 38 . An increase in the mRNA expression of the Il10 gene, which is a well-known anti-inflammatory cytokine, after APAP administration was reported in mice 30 , 31 . Kanno et al showed that mRNA levels of the Il10 gene in the blood were higher in mice with more severe APAP-induced toxicity 31 ; therefore, the decreased Il10 level in the EEBGP group might be largely attributable to the decreased necrosis rather than a direct effect of EEBGP on Il10 expression in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, when inflammation was caused by hepatic damage, anti-inflammatory cytokines as well as pro-inflammatory cytokines were induced 37 , 38 . An increase in the mRNA expression of the Il10 gene, which is a well-known anti-inflammatory cytokine, after APAP administration was reported in mice 30 , 31 . Kanno et al showed that mRNA levels of the Il10 gene in the blood were higher in mice with more severe APAP-induced toxicity 31 ; therefore, the decreased Il10 level in the EEBGP group might be largely attributable to the decreased necrosis rather than a direct effect of EEBGP on Il10 expression in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…However, massive activation of an inflammatory response impairs normal hepatocytes, resulting in expansion of the necrosis area 23 , 24 , 25 . Increased levels of cytokines such as interleukin (IL)-1β, IL-6, and IL-10 and chemokines such as CC-motif chemokine ligand 2 (CCL2) and CXC-motif chemokine ligand 2 (CXCL2) were observed in the liver after APAP administration 26 , 27 , 28 , 29 , 30 , 31 . APAP-induced hepatocellular necrosis in mice decreased when IL-1β production or signaling 26 , 27 , 28 or CCL2 signaling 29 was disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of mRNA were quantified using RT-qPCR according to our previously described methods ( 14 ). The animals were acclimated for 5–7 days prior to a pre-dose blood draw.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, animals overexpressing plasma GPx have strong resistance to APAP-induced hepatotoxicity ( 13 ). We have recently shown in mice that, among isozymes of GPx, the degree of APAP-induced hepatotoxicity depends on the mRNA expression levels of GPx3 in the blood ( 14 ). This finding therefore raises the question as to whether the gender difference in the GPx3 level contributes to the difference in APAP-induced hepatotoxicity between genders.…”
Section: Introductionmentioning
confidence: 99%
“…Paracetamol (PC) is a commonly used as analgesic and antipyretic drug [1]. It is safe at therapeutic levels, but at high doses it can lead to undesirable side effects such as hepatotoxicity and nephrotoxicity [2].…”
Section: Introductionmentioning
confidence: 99%